FINTECH AND BANK: PAST, PRESENT, AND FUTURE - Mercurius Broto Legowo; Steph Subanidja; Fangky Antoneus Sorongan (JURNAL TEKNIK KOMPUTER, 2021)
Financial Technology has long been applied to the financial and banking sectors until the emergence of financial technology innovation called FinTech. Referring to the evolution of FinTech until now, FinTech influences the Bank's activities from the past, present, and future. Based on these facts, this research aims to present a descriptive analysis of FinTech and Bank in the past, present, and future, especially in Indonesia as a case study.  This study uses a descriptive analysis research method and using qualitative method approaches. This descriptive analysis is carried out by critically reviewing various relevant scientific journals, the facts of the FinTech phenomenon in Indonesia, and documentation papers from banking institutions. The results of this analysis reveal what happened to FinTech and the Bank in the past, present, and future. The contributions from this study can provide insight and understanding related to FinTech and banks in the past, present, and future more in-depth.